The Effect of Enterprise Resource Planning (ERP) on Performance with Information Technology Capability as Moderating Variable - Almatius Setya Marsudi; Rilo Pambudi (Journal of Economics, Business, and Accountancy Ventura, 2021)
This study aims to gain an understanding of the role of technological capability as a moderating variable on the effect of ERP implementation on operational performance. Companies are expected to utilize information technology capability to encourage the sustainability of information technology developments. This study used secondary data from companies that have implemented ERP in Indonesia. The data were tested for validity and reliability and classical assumptions. It used moderated regression analysis by considering technological capability as a moderating variable. The sample taken consists of companies in Indonesia that have used ERP for at least three years. The result indicates that there is an effect ERP implementation on operational performance but there is no effect of technology capability as a moderating variable on the effect of ERP implementation on operational performance. This study provides theoretical and practical contributions by explaining how to build IT capability so that the implementation of ERP drives the operational performance of business processes. This implies the importance of companies implementing ERP and understanding ERP development systems such as good corporate strategies, executive support, and changes in business processes. The results of this study imply that there are factors that strengthen or weaken the effect of ERP implementation on operational performance in addition to IT capabilities.